Aligned nanofiber material supports cell growth and increases osteogenesis in canine adipose‐derived mesenchymal stem cells in vitro. Issue 7 (6th March 2018) - Pandey, Sony; Rathore, Kusum; Johnson, Jed; Cekanova, Maria
Abstract: Tissue engineering shows great promise for the treatment of degenerative diseases, including bone repair. Polymer nanofibers provide a three‐dimensional (3‐D) scaffold for attachment and growth of mesenchymal stem cells. Increasing evidence supports that fiber alignment on scaffolds plays a major role in the viability and differentiation of stem cells. We compared the cell viability of canine adipose tissue‐derived mesenchymal stem cells (cADMSCs) cultured in the aligned‐ (NanoAligned™) and random‐ (NanoECM™) oriented polycaprolactone (PCL) nanofiber‐coated plates to control polystyrene tissue culture plates using a proliferation assay. Ability of the plates to induce differentiation of cADMSCs into osteocytes, adipocytes, and neurons was evaluated based on expression of the osteocyte markers, COL1A1 and osterix ; adipocyte markers PPARγ2 and LPL ; and neuronal marker nestin using RT‐PCR. Proliferation results demonstrated that aligned‐oriented PCL nanofiber‐coated plates were more suitable substrate for cADMSCs after 7 days in culture compared to random‐oriented PCL nanofiber‐coated or control plates. Additionally, we demonstrated that both 3‐D PCL nanofiber‐coated plates were a better scaffold for cADMSCs differentiation into osteocytes compared to control plates. In conclusion, our results confirm that PCL nanofiber is a suitable tissue engineering material for use in regenerative medicine for canine patients in vivo . © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1780–1788, 2018.